Research Parasites Are Beneficial for the Organism as a Whole: Competition between Researchers Creates a Symbiotic Relationship - Benedikt Fecher; Gert G. Wagner (Institute for the Study of Labor (IZA), 2016)
In the New England Journal of Medicine, Longo and Drazen critically assessed the concept of data sharing. Their main concern is that a "new class of research person will emerge" that uses data, which were gathered by other researchers, for their own original research questions. The authors referred to this class of researcher as "research parasites". Longo and Drazen are right when they note that scientific data sharing deserves more recognition. However, they indicate that the most adequate form of recognition for data sharing is coauthorship. They suggest to work "symbiotically, rather than parasitically, with the investigators holding the data, moving the field forward in a way that neither group could have done on its own." Although this is true in particular cases, co-authorship as the sole instrument of credit will unnecessarily restrict the potential of data sharing. More suitable instruments for giving credit where credit is due would be a much greater appreciation of data sharing by research communities by introducing citations of data sets, bestowing awards for good datasets, and considering data "production" when assessing scientists' career prospects, funding applications, and research outputs.
Keywords: B40; C80; Z11; 330; organism; rewards; incentives; data sharing; culture